Far‐field pressurization likely caused one of the largest injection induced earthquakes by reactivating a large preexisting basement fault structure. Issue 19 (11th October 2016) - Yeck, W. L.; Weingarten, M.; Benz, H. M.; McNamara, D. E.; Bergman, E. A.; Herrmann, R. B.; Rubinstein, J. L.; Earle, P. S.
Abstract: The Mw  5.1 Fairview, Oklahoma, earthquake on 13 February 2016 and its associated seismicity produced the largest moment release in the central and eastern United States since the 2011 Mw  5.7 Prague, Oklahoma, earthquake sequence and is one of the largest earthquakes potentially linked to wastewater injection. This energetic sequence has produced five earthquakes with Mw  4.4 or larger. Almost all of these earthquakes occur in Precambrian basement on a partially unmapped 14 km long fault. Regional injection into the Arbuckle Group increased approximately sevenfold in the 36 months prior to the start of the sequence (January 2015). We suggest far‐field pressurization from clustered, high‐rate wells greater than 12 km from this sequence induced these earthquakes. As compared to the Fairview sequence, seismicity is diffuse near high‐rate wells, where pressure changes are expected to be largest. This points to the critical role that preexisting faults play in the occurrence of large induced earthquakes. Key Points: One of the largest injection‐related earthquakes was likely induced by far‐field pressurization near Fairview, Oklahoma Earthquakes occur in Precambrian basement, 6‐10 km below sea level, on a partially unmapped fault Observations point to the critical role optimally oriented preexisting faults play in the occurrence of large induced earthquakes